Conversion of Methane Facilitated by Solid Oxide Electrolysis Cells. Issue 10 (30th July 2020) - Liu, Kefeng; Meng, Fei; Zhu, Di; Wang, Zi; Lou, Shujie; Zhao, Jing; Xiao, Haicheng; Tang, Yongchun
Abstract: A novel Fe‐Al/SiO2 catalyst for direct non‐oxidative conversion of methane to ethylene, benzene, and naphthalene was synthesized. An Fe‐Al/SiO2 catalyst integrated solid oxide electrolysis cell (SOEC) membrane reactor design is further developed. It could be successfully demonstrated that the SOEC enabled the in situ removal of H2, which helps to shift the chemical equilibrium of the methane conversion reaction to enhance the conversion efficiency. Abstract : The synthesis of a novel Fe‐Al/SiO2 catalyst for direct non‐oxidative conversion of methane to ethylene, benzene, and naphthalene is described. Using solid oxide electrolysis cell devices to remove hydrogen effectively from the reaction system helps to improve the efficiency of a non‐oxidative methane conversion process, shifting the reaction equilibrium and boosting the methane conversion.